PERCEPTION–PRACTICE GAPS IN BLENDED LEARNING: ENGLISH TEACHERS’ PRACTICES AND CHALLENGES IN TEACHING WRITING AT ADDIS ABABA UNIVERSITY - Agmasie Tarekegn Mekonnen; Hailom Banteyerga Amaha (Universitas Islam Sumatera Utara (UISU), 2026)
Blended learning (BL) has been widely recognized as a promising approach for enhancing English language teaching and learning. This study investigated the perception–practice gap in blended learning implementation among English language teachers at Addis Ababa University, particularly in teaching writing skills. A convergent mixed-methods design was employed by combining survey data collected from 31 English language teachers with semi-structured interviews conducted with six participants. Quantitative and qualitative data were analyzed separately and later integrated to provide a comprehensive understanding of teachers’ perceptions and classroom practices. The findings revealed that teachers valued blended learning for improving student motivation, flexibility, learner autonomy, and access to learning resources. However, its actual implementation remained limited and largely informal. In practice, blended learning was mainly restricted to material sharing, task assignment, and communication through messaging applications. Major challenges include unreliable internet connectivity, inadequate technological infrastructure, insufficient practical training, and weak institutional support as key contributors to the perception–practice gap. The findings suggest that successful blended learning implementation requires institutional investment in technological infrastructure, sustained professional development, and stronger policy support. The study contributes to current discussions on technology integration in English language teaching by highlighting the contextual realities of blended writing instruction in Ethiopian higher education.